HAEMORRHOIDAL ARTERY LIGATION OPERATION WITHOUT DOPPLER GUIDANCE - Naqvi, Syeda Rifaat Qamar; Naqvi, Syeda Saima Qamar; Rashid, Muhammad Misbah; Sheikh, Irfan Ali; Ali, Muhammad; Nafees, Abu ul Ala (Journal of Ayub Medical College Abbottabad, 2019)
Background: A range of surgical options from banding to open haemorrhoidectomy are available for the treatment of haemorrhoids. Haemorrhoidal artery ligation operation (HALO) with or without Doppler guidance is a newer option with claims of having better efficacy. We aimed to study the efficacy of HALO without Doppler guidance in terms of presence of postoperative complications including pain, bleeding, prolapse and overall patient satisfaction. Methods: This interventional study was conducted in the Department of Surgery Combined Military Hospital Rawalpindi, from 1st September 2013 to 31st July 2015. Consenting patients with second degree haemorrhoids not responding to banding or sclera-therapy and those with third and fourth degree haemorrhoids were included in the study. They were followed up at 1 week, 6 weeks and then at 6 months. All of them were questioned regarding pain, bleeding, prolapse and overall satisfaction with the procedure. Results: A total of 97 patients (n=97) were included in the study. At 1 week follow up after HALO, mean pain score was 1.76, at 6 weeks it was 0.4 and at 6 months none of the patients had any pain. Postoperative bleeding was seen in 1 patient at 1 week (1.03%). None of the patients had bleeding at 6 weeks (0%), and 2 patients reported mild occasional bleeding at 6 months’ post op (2.06%). Four of our patients had persistent prolapse post-operatively (4.12%) which persisted throughout follow up. Ninety-four (96.91%) patients were overall satisfied with the procedure, whereas 3 patients (3.09%) were not satisfied. Conclusion: Haemorrhoidal artery ligation operation without Doppler guidance is an effective method to treat haemorrhoids in terms of post-operative pain, bleeding and patient satisfaction. Keywords: HALO; Haemorrhoids; Doppler probe